68Ga-PSMA PET/CT Uptake in the Ureter Caused by Ligand Expression in Urothelial Cancer. (January 2020) - Zacho, Helle D.; Pedersen, Sine H.; Petersen, Astrid; Petersen, Lars J.
Abstract : Abstract: 68 Ga-PSMA PET/CT has become a well-established imaging modality to detect prostate cancer (PCa) metastases in biochemical recurrence. Despite its claimed specificity for PCa, 68 Ga-PSMA uptake in tissues unrelated to PCa, particularly in the neovascular tissue of other cancers, has been reported in numerous studies. A 73-year-old man underwent 68 Ga-PSMA PET/CT for biochemical recurrence of PCa 7 years after radical prostatectomy. The 68 Ga-PSMA PET/CT showed 1 lesion with PSMA uptake in the distal left ureter. Histology revealed a low-grade noninvasive papillary urothelial carcinoma. By immunohistochemistry, PSMA expression was observed in the neoplastic urothelial cells and in the vessels of the papillary structures.